Characterization of Global Research Trends and Prospects on Single-Cell Sequencing Technology: Bibliometric Analysis - Quan Wang; Ke-Lu Yang; Zhen Zhang; Zhu Wang; Chen Li; Lun Li; Jin-Hui Tian; Ying-Jiang Ye; Shan Wang; Ke-Wei Jiang (JMIR Publications, 2021)
BackgroundAs single-cell sequencing technology has been gradually introduced, it is essential to characterize global collaboration networks and map development trends over the past 20 years. ObjectiveThe aim of this paper was to illustrate collaboration in the field of single-cell sequencing methods and explore key topics and future directions. MethodsBibliometric analyses were conducted with CiteSpace and VOSviewer software on publications prior to November 2019 from the Web of Science Core Collection about single-cell sequencing methods. ResultsUltimately, we identified 2489 records, which were published in 495 journals by 14,202 authors from 1970 institutes in 61 countries. There was a noticeable increase in publications in 2014. The United States and high-income countries in Europe contributed to most of the records included. Harvard University, Stanford University, Karolinska Institutes, Peking University, and the University of Washington were the biggest nodes in every cluster of the collaboration network, and SA Teichmann, JC Marioni, A Regev, and FC Tang were the top-producing authors. Keywords co-occurrence analysis suggested applications in immunology as a developing research trend. ConclusionsWe concluded that the global collaboration network was unformed and that high-income countries contributed more to the rapidly growth of publications of single-cell sequencing technology. Furthermore, the application in immunology might be the next research hotspot and developmental direction.